Transformational Leadership, Compensation, Work Environment and Employee Performance: The Mediating Role of Job Satisfaction - Purnomo, Joko; Helmy, Irfan; Andri, Gus (AIBPM Publisher, 2024)
This study scrutinizes the link between transformational leadership, compensation, work environment, and employee performance. In addition, job satisfaction was also investigated as a mediating variable. A total of 57 employees of Perum Perhutani Kebumen were involved in the survey from September 2023 to November 2023. Data analysis in this study was carried out using Smart Partial Least Squares (PLS) 3rd version. Questionnaires were employed in the survey process. The result revealed that transformational leadership and compensation display positively affect employee performance. In contrast, this study also indicates that the non-physical environment has an insignificant effect on job satisfaction and employee performance. Furthermore, based on the specific indirect effect, this study also found that job satisfaction shares a mediating effect in the connection between transformational leadership and employee performance. Job satisfaction also has a mediating effect on the compensation-employee performance connection. This research suggests both practical and theoretical implications regarding how to improve employee performance